Anti-IL-6 Receptor Antibody Causes Less Promotion of Tuberculosis Infection than Anti-TNF-𝛼 Antibody in Mice - Masaji Okada; Yoko Kita; Noriko Kanamaru; Satomi Hashimoto; Yasushi Uchiyama; Masahiko Mihara; Yoshikazu Inoue; Yoshiyuki Ohsugi; Tadamitsu Kishimoto; Mitsunori Sakatani (Clinical and Developmental Immunology)
Objective. Our aim was to investigate the effects of IL-6 blockade on the progression of Mycobacterium tuberculosis (TB) and compare them with those of TNF-α blockade in mice. Methods. Mice were intravenously infected with TB and injected with antibodies. Survival was monitored and histological and immunological studies were carried out. Results. All anti-IL-6R Ab-treated mice and 8 of 10 control mice survived until sacrificed 224 days after TB challenge, whereas anti-TNF-α Ab-treated mice all died between 120 and 181 days. Anti-IL-6R Ab-treated mice exhibited no significant differences in TB CFU in organs, including the lungs, and no deterioration in histopathology compared to control mice at 4 weeks. In contrast, anti-TNF-α Ab-treated mice exhibited increased TB CFU and greater progression of histopathological findings in organs than control mice. Spleen cells from anti-TNF-α Ab-treated mice had decreased antigen-specific response in IFN-γ release and proliferation assays. The results in anti-IL-6R Ab-treated mice suggest that spleen cell responses were decreased to a lesser degree. Similar results were obtained in IL-6 knockout (KO) mice, compared with TNF receptor 1 (TNFR1) KO and TNFR1/IL-6 double KO (DKO) mice. Conclusion. IL-6R blockade promotes the progression of TB infection in mice far less than TNF-α blockade.